Fertility Rates and Skill Distribution in Razin and Sadka's Migration-Pension Model: A Note - Tim Krieger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
Razin and Sadka (1999) show that unskilled immigration is beneficial to all income and all age groups in society, even if immigrants are net beneficiaries of the welfare system. Among other things, this result rests on the assumptions that immigrants have the same reproduction rate as the native population and that the immigrants' offspring has the same distribution of skills as the natives' offspring. By relaxing these assumptions, we show that the Razin and Sadka result is no longer unambiguous.
urn:nbn:de:bvb:19-epub-82-0
Keywords: H55; J61; 330; fertility rates; immigration policy; public pensions; Fertilität; Zuwanderungspolitik; Rentenversicherung